Tim Rogan. The Moral Economists: R. H. Tawney, Karl Polanyi, E. P. Thompson, and the Critique of Capitalism. - Dale, Gareth (The American Historical Review, 2019)
When the capitalist system hits the rocks and neoclassical economics loses its aura, alternative traditions invite attention. Tim Rogan’s The Moral Economists i
History
Keywords: The Moral Economists: R.H. Tawney; Karl Polanyi; E.P. Thompson; and the Critique of Capitalism (book); book review; capitalism

The Double Movement Ten Years After the Fall of Lehman Brothers - Vidal, Gregorio; Marshall, Wesley C. (Journal of Economic Issues (Taylor & Francis Ltd), 2019)
Ten years after the collapse of Lehman Brothers and the sharpest moments of panic within the global—and particularly the United States banking system—a somewhat strange dynamic has appeared. While the principal agents behind the crisis have collapsed their own institutions, the markets that they dominated, and even provoked what has been called the third crisis of economic theory, their political power has not waned. This theme has been well addressed by some academics such as Philip Mirowski (2013), while it has flummoxed others. In this article, we will argue that Karl Polanyi's theory of the "double movement" offers a coherent framework that is able to account for the history of the last ten years. Polanyi argues that different groups and members of society seek protection from the market, and that this search for protection has been the driving force between historical change. Polanyi does not ignore class; rather, he argues that different social classes can protect themselves in more or less effective ways. We argue that during the last ten years, the interests of globalized financial capital have been able to protect themselves with utmost effectiveness, while all other classes have been trammeled, often not even recognizing how or why actions are taken against the general interest.
Economics; History
Keywords: Lehman Brothers; capital market; double movement; financial crisis; financial markets; securities; stock exchanges; stocks (finance)

La società di mercato e le sue trasformazioni. Attualità di Karl Polanyi - Cangiani, Michele (Itinerari di ricerca storica, 2019)
ItIl neoliberalismo è sorto dall'esigenza di superare la crisi degli anni Settanta del secolo scorso, ma ha portato a una nuova crisi, da molti detta "sistemica". Siamo quindi sollecitati a riflettere sulle caratteristiche fondamentali del nostro sistema sociale e sulla sua storia. A questo fine, l'opera di Karl Polanyi fornisce preziose indicazioni. In essa, da una parte, la società di mercatocapitalistica viene definita in generale, nella sua specificità, mediante una comparazione a vasto raggio con le società precedenti. D'altra parte, viene analizzata la "trasformazione" di tale società da un assetto istituzionale all'altro, attraverso un periodo di crisi e di conflitto sociale. Poiché, tuttavia, le ragioni profonde della crisi permangono nel nuovo assetto insieme con le caratteristiche più generali del sistema sociale, la crisi tende a ripresentarsi, insieme all'esigenza di una nuova trasformazione istituzionale. Questo articolo intende mostrare che tale tesi è perlomeno implicita negli scritti di Polanyi e che quindi non solo la sua teoria della società di mercato in generale, ma anche le sue analisi delle vicende della "grande trasformazione" fra le due guerre mondiali possono essere utili per comprendere gli sviluppi ulteriori della nostra società fino alla situazione attuale.EnNeoliberalism arose from the need to overcome the crisis of the 1970s, but led to a new "systemic" crisis. We are therefore urged to reflect on the fundamental characteristics of our social system and its history. To this end, Karl Polanyi's work provides valuable suggestions. In it, on the one hand, the capitalist market society is defined in general, in its specificity, through a widerange comparison with previous societies. On the other hand, the "transformation" of that society is analyzed, from one institutional setup to another, through periods of crisis and social conflict. Since the deep reasons of the crisis remain in the new set-up, together with the more general characteristics of the social system, the crisis tends to recur, together with the need for a new institutional transformation. The present paper intends to show that this thesis is, at least, implicit in Polanyi's writings; therefore, not only his theory of the market society in general, but also his analysis of the events of the "great transformation" between the two world wars can be useful in understanding further developments of our society up to the current situation.
History
Keywords: capitalism; capitalismo; crisi; crisis; transformation; trasformazione